“Determinación del distanciamiento optimo y época oportuna de aporque en mani (arachis hipogaea L.) variedad blanco tarapoto, en el distrito de Juan Guerra-Provincia de San Martín” - Ushiñahua Hidalgo, Segundo Jacob (2002)
The aim of the project was to detennine the effect and planting distance and harvesting time on the production of Arachis hipogaea L. "Blanco Tarapoto" peanut. The field work was done at the Experimental Station "El Provenir'', San Martín. We used a BCR in an factorial design 0,20 m x 0,80 m and 0,20 m x 0,60 m and six harvesting time 40, 60, 25 days after planting (dds). Treatments 0,20 x 0,60 at 25 and 40 dds and 0,20 x 0,60 at 40 dds reached high production with 1986.98 kg/ha and 1906.25 kg/ha respectively. Treatments 0,20 x 0,60 at 40 dds get the SI. 927,25 maximun net profits and 1,54 cost relationship. Results show that 40 dds harvest time and 0,20 m x 0,60 m is the best.